Mechanical characteristic and biological behaviour of implanted and restorative bioglasses used in medicine and dentistry: A systematic review. Issue 6 (June 2017) - Lizzi, F.; Villat, C.; Attik, N.; Jackson, P.; Grosgogeat, B.; Goutaudier, C.
Abstract: Objective: Nowadays bioactive glasses are finding increasing applications in medical practice due to their ability to stimulate re-mineralisation. However, they are intrinsically brittle materials and the study of new compositions will open up new scenarios enhancing their mechanical properties and maintaining the high bioactivity for a broader range of applications. This systematic review aims to identify the relationship between the composition of bioactive glasses used in medical applications and their influence on the mechanical and biological properties. Methods: Various electronic databases (PubMed, Science Direct) were used for collecting articles on this subject. This research includes papers from January 2011 to March 2016. PRISMA guidelines for systematic review and meta-analysis have been used. 109 abstracts were collected and screened, 68 articles were read as relevant articles and a total of 22 papers were finally selected for this study. Results: Most of the studies obtained enhanced mechanical properties and the conservation of bioactivity behaviours; although a lack of homogeneity in the characterization methods makes it difficult to compare data. Significance: New compositions of bioactive glasses incorporating specific ions and the addition in polymers will be the most important direction for future researches in developing new materials for medical applications and especially for dentistry.